The Effectiveness of A Task-Based Learning Strategy Through The Quizizz Application On To Enhance Students’ Achievement And Motivation In Reading Classroom - Hidayati, Anik; Sri Wuli Fitriati; Katharina Rustipa (English Education Journal, 2023)
The study aims to investigate how using the Quizizz application to apply a task-based learning technique will improve the achievement and motivation of students in teaching reading. This study will use sequential explanatory designs that combine quantitative and qualitative methods. It only has one eighth-grade class at one school: SMPN N 1 Bawen Kab. Semarang. Thirty-six pupils were to participate. Pre and post-tests, observations, and questionnaires are used to gather data. Students' reading comprehension achievement was estimated using their pre-and post-test results. A questionnaire and observation were utilized to assess the impact on student motivation. A questionnaire and observation were utilized to assess the impact on student motivation. Pre-test and post-test data will be used to conduct the analysis. The researcher will be using SPSS 22 for Windows. The study's significance level is 0.000, which is less than 0.05. If the sig. is <0.05. The average pre-test score was 58.89, whereas the post-test score was 74.58. It grew by 15.69. The questionnaire revealed that 86% of respondents thought it had a favorable effect, while 14% didn't. The observation supports the facts. This study demonstrated that TBL, using a Quizizz application, might improve the achievement and motivation of students in teaching reading.